A criança e a ludicidade: uma experiência na escola Maximiano Antônio Rodrigues - MARQUES, Maria do Socorro Cardoso (2024)
This work presents a research carried out with children from the children 's education at the Maximiano Antonio Rodrigues School located at PA 151 km 04, community of Murutinga, municipality of Abaetetuba / Pa. This research focuses on playfulness in children's education, more precisely the songs of the roda as a sung play and a methodological strategy that favors the teaching of children's learning. In addition, it also seeks to promote the cultural rescue of this play so old but little used today. Therefore, the objective of this research is to analyze the use of the cantigas of roda as methodological process lúdico the learning teaching process of the children's education students of the above mentioned school. It also seeks to encourage the posture of the literacy teacher in relation to the use of games, games and songs in everyday school, as well as to analyze the strategies used by the teacher in the use of play activities as mediators of the learning process in school everyday. Knowing the relation between the teacher's practice and the expectations of the students in relation to the ludic activities.